On Computation of Entropy of Hex-Derived Network - Pingping Song; Haidar Ali; Muhammad Ahsan Binyamin; Bilal Ali; Jia-Bao Liu (Complexity)
A graph’s entropy is a functional one, based on both the graph itself and the distribution of probability on its vertex set. In the theory of information, graph entropy has its origins. Hex-derived networks have a variety of important applications in medication store, hardware, and system administration. In this article, we discuss hex-derived network of type 1 and 2, written as HDN 1n and HDN 2n, respectively of order n. We also compute some degree-based entropies such as Randić, ABC, and GA entropy of HDN 1n and HDN 2n.